English Medium Instruction: comparing teacher beliefs in secondary and tertiary education - Briggs, J; Dearden, J; Macaro, E (Adam Mickiewicz University, Faculty of Pedagogy and Fine Arts, Department of English Studies, 2018)
Learning content through the medium of a second language is a form of education which is growing rapidly in both secondary and tertiary educational phases. Yet although considerable research now exists on these phases of education viewed separately, virtually no comparisons have been made between the two phases. This study compared beliefs about English Medium Instruction (EMI) held by n=167 secondary and tertiary EMI teachers from 27 countries. Teachers’ beliefs were elicited in four key areas: EMI teachers’ goals; EMI policy; benefits and drawbacks to students; and challenges to teachers. The findings indicate that secondary teachers felt more strongly that EMI provides students with a high quality education. More secondary than tertiary teachers reported an institutional policy on the English proficiency level required to teach through EMI, yet in neither phase was there evidence of adequate support to reach a required proficiency level. Teachers deemed EMI beneficial to advancing students’ English but felt that EMI would affect academic content, with no clear difference between the phases. Our conclusions indicate that EMI is being introduced without thorough institutional stakeholder discussion and therefore without clear policies on levels of teacher expertise. Neither is there evidence of a dialogue between phases regarding the challenges faced by EMI teachers and students.